2010
DOI: 10.1002/jcc.21512
|View full text |Cite
|
Sign up to set email alerts
|

Redox‐induced configuration conversion for thioacetamide dimer can function as a molecular switch

Abstract: The electronic switching properties of thioacetamide dimer (TAD) were investigated using the nonequilibrium Green's function method combined with density functional theory for design of a novel molecular switch. The H-bonded TAD can be converted upon hole-trapping to a three-electron (3e)-bonded configuration with a S [symbol: see text] S linkage which could provide a more favorable channel for charge transfer than the before. The redox-induced configuration conversion between the H-bonded and the 3e-bonded TA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Accordingly, it seems probable that transmission in a decylcarbazole (6) structure could be modulated substantially by gate voltage without incurring any form of gate leakage for biases in the range of −1 to 4 V. It is thus suggested that proper isolation of the π-stack by an adequate alkyl chain dielectric imparts the possibility for σ−π molecular structures to operate as true transistor devices. It should be noted that these observations concern systems modeled at 0 K. Deviations from the reported behavior at higher temperatures may arise due to phonon scattering.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Accordingly, it seems probable that transmission in a decylcarbazole (6) structure could be modulated substantially by gate voltage without incurring any form of gate leakage for biases in the range of −1 to 4 V. It is thus suggested that proper isolation of the π-stack by an adequate alkyl chain dielectric imparts the possibility for σ−π molecular structures to operate as true transistor devices. It should be noted that these observations concern systems modeled at 0 K. Deviations from the reported behavior at higher temperatures may arise due to phonon scattering.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Device structures with π-stacked wires of length n = 6 are displayed in Figure 1. A complete device layout, illustrating the left and right electrode regions and central scattering region for ethylcarbazole (6), is depicted in Figure 2.…”
Section: ■ Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The conformational flexibility in structures of bio−entities including nucleic acids, carbohydrates, peptides, and their mimetics, make them a versatile tool in the area of molecular switches, which can be controlled by external stimuli like pH, optical, electrical, and electrochemical pulses. Many experimental and theoretical methods have been devoted to realise molecular switches among biomolecules and their synthetic analogues Molecular switching triggered using redox phenomenon is advantageous over others of its kind for being reversible for many cycles.…”
Section: Introductionmentioning
confidence: 99%